Effect of Pot Size on Various Characteristics Related to Photosynthetic Matter Production in Soybean Plants - Minobu Kasai; Keisuke Koide; Yuya Ichikawa (International Journal of Agronomy)
Despite the wide uses of potted plants, information on how pot size affects plant photosynthetic matter production is still considerably limited. This study investigated with soybean plants how transplantation into larger pots affects various characteristics related to photosynthetic matter production. The transplantation was analyzed to increase leaf photosynthetic rate, transpiration rate, and stomatal conductance without affecting significantly leaf intercellular CO2 concentration, implicating that the transplantation induced equal increases in the rate of CO2 diffusion via leaf stomata and the rate of CO2 fixation in leaf photosynthetic cells. Analyses of Rubisco activity and contents of a substrate (ribulose-1,5-bisphosphate (RuBP)) for Rubisco and total protein in leaf suggested that an increase in leaf Rubisco activity, which is likely to result from an increase in leaf Rubisco content, could contribute to the transplantation-induced increase in leaf photosynthetic rate. Analyses of leaf major photosynthetic carbohydrates and dry weights of source and sink organs revealed that transplantation increased plant sink capacity that uses leaf starch, inducing a decrease in leaf starch content and an increase in whole plant growth, particularly, growth of sink organs. Previously, in the same soybean species, it was demonstrated that negative correlation exists between leaf starch content and photosynthetic rate and that accumulation of starch in leaf decreases the rate of CO2 diffusion within leaf. Thus, it was suggested that the transplantation-induced increase in plant sink capacity decreasing leaf starch content could cause the transplantation-induced increase in leaf photosynthetic rate by inducing an increase in the rate of CO2 diffusion within leaf and thereby substantiating an increase in leaf Rubisco activity in vivo. It was therefore concluded that transplantation of soybean plants into larger pots attempted in this study increased the plant photosynthetic matter production by increasing mainly sink capacity that uses leaf starch for whole plant growth, particularly, growth of sink organs.